2023
DOI: 10.1039/d2ob02099h
|View full text |Cite
|
Sign up to set email alerts
|

Effective carrier-free gene-silencing activity of sphingosine-modified siRNAs

Abstract: RNA interference (RNAi) is a natural cellular process that silences the expression of target genes in a sequence-specific way by mediating targeted mRNA degradation. One of the main challenges in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, most of the previous studies reported the conjugation at terminal position while some including lipid conjugation at non-terminal positions, to obtain effective gene silencing in carrier-free mode. [29][30][31][32][33] Therefore, we envisioned spermine modication at the non-terminal position by conjugation with a linker at the 4 ′ -C position of the modied nucleoside. We hypothesized that such a conjugated system would not alter the overall physical structure of the duplex and would exhibit conserved gene silencing with improved stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies reported the conjugation at terminal position while some including lipid conjugation at non-terminal positions, to obtain effective gene silencing in carrier-free mode. [29][30][31][32][33] Therefore, we envisioned spermine modication at the non-terminal position by conjugation with a linker at the 4 ′ -C position of the modied nucleoside. We hypothesized that such a conjugated system would not alter the overall physical structure of the duplex and would exhibit conserved gene silencing with improved stability.…”
Section: Introductionmentioning
confidence: 99%